Pengaruh Pelayanan Persalinan terhadap Kepuasan Pengguna Pelayanan Persalinan (Studi Evaluasi) di Puskesmas Mayong H Kabupaten Jepara - Madyo Eri Mulyono, Djaswadi Dasuki, Mohammad Hakimi (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Maternal mortality depends much on health service quality especially pregnancy care and delivery attendant. Therefore, the availability of professional attendant at delivery is really needed and midwife is one of the options. In reality, delivery service by birth attendants is still of interest to the community. To close this gap, there should be collaboration between midwives and birth attendants, known as companion delivery.Objectives: To find out the effect of companion delivery on the consumers' satisfaction of delivery service.Methods: This was static group comparisson. One community health center served as the treatment group (companion delivery) and another community health center as the control group (birth attendants). The respondents of the treatment and control groups were 83 mothers with newborn babies. Samples were taken proportionally. The analysis used were chi-square test, t-test and the multiple-regression analysis using SPSS-10 program, with 5% significance level.Results: There was significant difference between consumers' satisfaction of companion delivery and consumers' satisfaction of delivery by birth attendants